Preparation and photoelectric properties of cadmium sulfide quantum dots - Vincent Teng (Chinese Physics B, 2019)
Cadmium sulfide quantum dots (CdS QDs) are widely used in solar cells, light emitting diodes, photocatalysis, and biological imaging because of their unique optical and electrical properties. However, there are some drawbacks in existing preparation techniques for CdS QDs, such as protection of inert gas, lengthy reaction time, high reaction temperature, poor crystallinity, and non-uniform particle size distribution. In this study, we prepared CdS QDs by liquid phase synthesis under ambient room temperature and atmospheric pressure using sodium alkyl sulfonate, CdCl2, and Na2S as capping agent, cadmium, and sulfur sources respectively. This technique offers facile preparation, efficient reaction, low-cost, and controllable particle size. The as-prepared CdS QDs exhibited good crystallinity, excellent monodispersity, and uniform particle size. The responsivity of CdS QDs-based photodetector is greater than $0.3\,{\rm{μ }}{\rm{A}}/{\rm{W}}$, which makes them suitable for use as ultra-violet (UV) detectors.